JOINT STOCK PRICE INDEX AND THE MOVEMENT OF THE RUPIAH EXCHANGE RATE DURING THE PANDEMIC - Juliasari, Deni (Jurnal Ilmu Manajemen Advantage, 2021)
The existence of the Corona Virus (Covid-19) pandemic event not only poses a threat to health but also to economic growth in a country. The impact of the spread of the Corona Virus (Covid-19) cannot be calculated with certainty. So this study aims to find out the difference between the JCI and the Rupiah Exchange Rate before and after the pandemic on March 2, 2020. The analysis method uses a paired t-test. The population for this study are companies listed on the Indonesia Stock Exchange 2020. The sampling technique used is purposive sampling. Based on the results of data analysis and discussion, it can be concluded that there is a difference between the JCI before and after the COVID-19 pandemic. There is a significant difference in the Rupiah Exchange Rate in the events before and after the pandemic. The existence of the Corona Virus (Covid-19) pandemic event not only poses a threat to health but also to economic growth in a country. The impact of the spread of the Corona Virus (Covid-19) cannot be calculated with certainty. However, the slowdown in the economic system has been felt, especially in the industrial, tourism, trade, transportation and investment sectors. It is unavoidable as well as with Indonesia, the increase in positive cases of Corona has an effect on the stock market.